Bilateral Investment Treaties dan Penyelesaian Arbritase Internasional (Studi Kasus Pencabutan Izin Kuasa Pertambangan Churchill Mining) - Yacob Rihwanto (Lex Renaissance, 2016)
The aim of BITs is to protect the investment in foreign countries, enhance the market-oriented policy and create the practice of transparent and non-discriminant between state and investors.  This research studied about some issues: first, how is the impact of Bilateral Investment Treaties (BITs) on the investment climate in the developing countries particularly in Indonesia? Second, how is the process of conflict solution if there is a conflict in Bilateral Investment Treaties? This is a normative research using the regulation approach. The research concluded that first; the implementation of the agreement of BITs conducted by Indonesia at the moment has led Indonesia as the host country to the loss and the contract is no longer relevant and needs to be revised. Second if there is a conflict, it can be solved through ICSID as an arbitrary institution towards the lawsuit of investment between states signing the contract of BITs.    Keywords: Lawsuit, investment, international arbitration